White Matter Alterations in Cognitively Normal apoE ɛ2 Carriers: Insight into Alzheimer Resistance? - Chiang, G.C.; Zhan, W.; Schuff, N.; Weiner, M.W. (American Journal of Neuroradiology, 2012)
BACKGROUND AND PURPOSE: The basis for decreased vulnerability to AD among apoE ɛ2 carriers is unknown. The purpose of this study was to use diffusion tensor imaging to detect possible differences in white matter integrity between cognitively normal elderly apoE ɛ2 carriers and apoE ɛ3/ɛ3 controls. MATERIALS AND METHODS: Thirty-nine cognitively normal elderly individuals (19 heterozygous carriers of the apoE ɛ2 allele, 20 apoE ɛ3/ɛ3 subjects as controls) underwent diffusion tensor MR imaging on a 4T scanner. Fractional anisotropy, MD, and axial and radial diffusivity were compared using a ROI approach. In addition, an exploratory whole-brain analysis of fractional anisotropy between the 2 groups was undertaken using TBSS. RESULTS: apoE ɛ2 carriers had higher FA in the posterior cingulate white matter (P = .01) and anterior corpus callosum (P = .005) than apoE ɛ3/ɛ3 controls, secondary to lower radial diffusivity. No significant differences in the FA of the posterior corpus callosum, anterior cingulate white matter, or parahippocampal white matter were seen. Whole-brain TBSS analysis detected regions of higher FA in the apoE ɛ2 group in the superior longitudinal fasciculus, right thalamus, and the bilateral anterior limbs of the internal capsule, in addition to the posterior cingulum and corpus callosum (P < .005). There were no regions in which the apoE ɛ3/ɛ3 group had higher FA. CONCLUSIONS: apoE ɛ2 carriers harbor more robust white matter integrity that may be associated with decreased vulnerability to developing AD. This provides further evidence that regional DTI metrics may serve as early imaging biomarkers of AD risk. ADAlzheimer diseaseapoEapolipoprotein EFAfractional anisotropyMDmean diffusivityMMSEMini-Mental State ExaminationTBSStract-based spatial statistics